Strategi Komunikasi Pemerintah Kabupaten Karawang dalam Mensosialisasikan Program Beasiswa Karawang Cerdas - Komang Reisha Oktavian Wiraparamita Giri; Evi Priyanti; Hanny Purnamasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Achieving quality education and raising the Human Development Index (HDI) both depend heavily on education. When compared to other regions of West Java, Karawang Regency often has a low Human Development Index (HDI). As specified in Karawang Regent Regulation Number 45 of 2022 concerning the Karawang Cerdas Program, the Karawang Regency Government subsequently introduced a policy for education expense support in the form of the Karawang Cerdas scholarship program. The program's administration, including socialization, falls under the purview of the People's Welfare Section of the Karawang Regency Regional Secretariat. Finding, evaluating, and summarizing the social welfare communication approach used to promote the Karawang Cerdas Program is the goal of this study.This study is descriptive by design and employs a qualitative method using a qualitative approach. The results of the research demonstrate that the Karawang Cerdas Program is the communicator (who) in the Social Welfare communication strategy, along with Welfare, SKPD, and educational units; the communicants (to whom) are all societal levels; the media (in which channels) are direct media, print, social, and news; and the effect (with what effect) of the high number of registrants and the presence of extortion officers.